Peran Komunikasi Organisasi Pengurus Masjid Jami’ Al-Ilham dalam Pemberdayaan Lembaga Keagamaan Binaan - Farouq, Umar (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2025)
This study aims to describe and analyze the implementation of organizational communication carried out by the management of the Jami' Al-Ilham Mosque in an effort to empower the mosque, musala, and majlis taklim. Organizational communication is an important aspect in creating synergy, conveying the vision of the ummah, and building networks between religious institutions in the surrounding environment. This research uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation of the activities of mosque administrators and fostered partners. The results showed that the communication carried out was two-way and participatory, utilizing various formal and informal communication channels. The communication strategies applied include regular coordination meetings, the use of social media, and a family-based personal approach. The implementation of effective communication contributes to increasing the institutional capacity of the fostered partners, strengthening community solidarity, and expanding the reach of da'wah and social religious activities. This research recommends the importance of strengthening internal communication structures and developing technology-based communication media to support sustainable empowerment.